Metastatic oral squamous cell carcinoma in a captive common hippopotamus (Hippopotamus amphibius) - Oliveira, Ayisa R. de; Arenales, Alexandre; Carvalho, Thaynara P. de; Pessanha, Angela T.; Tinoco, Herlandes P.; Costa, Maria Elvira L. T. da; Paixão, Tatiane A. da; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2018)
Reported cases of neoplasia affecting hippopotamus are very scarce. This report describes a metastatic oral squamous cell carcinoma in a captive 44-year-old male common hippopotamus (Hippopotamus amphibius) that developed progressive loss of appetite, fibrinohemorrhagic oral discharge, and progressive weight loss. Gross, cytological, and histopathological findings were compatible with a conclusive diagnosis of an invasive oral squamous cell carcinoma with metastasis in the lung, adrenal, and spleen. To the best of our knowledge this is the first report of squamous cell carcinoma in a common hippopotamus.